THE RISK FACTORS FOR THE HYPERBILIRUBINEMIA INCIDENT IN NEONATES AT DR. RAMELAN HOSPITAL IN SURABAYA - Farida Triani; Bagus Setyoboedi; Budiono Budiono (UNIVERSITAS AIRLANGGA, 2022)
condition that often occurs in neonates. This condition is important to note, because if the bilirubin levels are too high, it can lead to several complications in the brain, such as encephalopathy and cerebral palsy in infants.Objective: The objective of this study is to analyze which maternal and neonatal risk factors can cause hyperbilirubinemia in neonates. Methods: This study is an analytical study with a cross sectional approach. Population samples was taken from the perinatology room Dr. Rumkital. Ramelan Surabaya in January 2018 - December 2019, there were 252 samples and 122 samples who experienced hyperbilirubinemia. Data analysis using Chi Square test and logistic regression. Results: It was found that the type of delivery with cesarean section was the largest percentage with a p value of 0.106;; Most LBW with p value 0.038; male at most with a p value of 0.046. From the results of multivariate analysis, it was found that the variable birth weight had a greater influence on the incidence of hyperbilirubinemia compared to other variables with a significance value of p value 0.00 on alpha 5%. Conclusion: There is a significant relationship between type of gestational age, sex and birth weight with the incidence of hyperbilirubinemia, while the type of delivery and parity have no significant relationship with the incidence of hyperbilirubinemiia. Keywords: Hyperbilirubinemia, Neonates, Risk Factor